2020
DOI: 10.1186/s12886-020-01533-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicone oil on peripapillary capillary density in patients with rhegmatogenous retinal detachment

Abstract: Purpose: To evaluate the effect of silicone oil (SO) on peripapillary blood flow using OCT angiography. Methods: This prospective case series recruited patients with unilateral rhegmatogenous retinal detachment (RRD) who underwent vitrectomy and SO tamponade. Patients were examined before SO removal and at 10 days, 1 month, and 3 months after SO removal on a spectral domain OCT angiography device (RTVue XR Avanti, Optovue Inc., CA, USA) for the measurement of radial peripapillary capillaries (RPC) vessel densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recently, Wang et al . [ 18 ] demonstrated that there was a mild increase in RPC VD in eyes with RRD after SO removal using OCTA, which suggested that SO tamponade might have adverse effects on RPC VD. The result was based on the assumption that RPC VD, which decreases in the eyes with RRD due to SO tamponade, will recover after SO removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al . [ 18 ] demonstrated that there was a mild increase in RPC VD in eyes with RRD after SO removal using OCTA, which suggested that SO tamponade might have adverse effects on RPC VD. The result was based on the assumption that RPC VD, which decreases in the eyes with RRD due to SO tamponade, will recover after SO removal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 15 16 17 ] We found only one study that examined the effect of SO on peripapillary VD in eyes with RRD. [ 18 ]…”
mentioning
confidence: 99%
“…The inside-disc zone was defined as an elliptical region corresponding to the boundary of the optic nerve. The peripapillary region was defined as the 2–4-mm annulus region extending from the inside-disc region and automatically divided into eight zones (Temporal Superior, Superior Temporal, Superior Nasal, Nasal Superior, Nasal Inferior, Inferior Nasal, Inferior Temporal, and Temporal Inferior, abbreviated as GH-TS, GH-ST, GH-SN, GH-NS, GH-NI, GH-IN, GH-IT, and GH-TI sections, respectively) according to the modified Garway-Heath (GH) grids ( 25 ). RPCs, the most superficial capillary layer, refer to the capillaries sited from the inner limiting membrane with an offset of 0 μm to the base of the nerve fiber layer, which corresponds to the thickness of the entire nerve fiber layer.…”
Section: Methodsmentioning
confidence: 99%
“…It is controversial whether increased IOP may have a role in SO-related peripapillary changes [ 146 , 170 , 171 ]. With regard to vascular changes, the radial peripapillary capillary (RPC) VD may decrease after SO tamponade [ 172 , 173 ], and this reduction may be more marked in the superior hemifield [ 173 , 174 ]. A progressive recovery of the RPC VD after ROSO, more marked in the superior sector, has been described by Wang et al [ 172 ].…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%
“…With regard to vascular changes, the radial peripapillary capillary (RPC) VD may decrease after SO tamponade [ 172 , 173 ], and this reduction may be more marked in the superior hemifield [ 173 , 174 ]. A progressive recovery of the RPC VD after ROSO, more marked in the superior sector, has been described by Wang et al [ 172 ]. Based on these differences between superior and inferior hemifield, it has been speculated that a negative mechanical effect of SO on peripapillary microvascular blood flow may be responsible [ 172 ].…”
Section: Retinal Changes Associated With Silicone Oilmentioning
confidence: 99%